Ceftaroline fosamil laden allograft: A new modality in reducing infection? - Singh, Vivek Ajit; Lim, Han Sim; Haseeb, Amber; Teh, Cindy Shuan Ju (SAGE Publications, 2018)
Purpose: Allograft infection remains the greatest challenge in orthopaedic reconstructive surgery especially methicillin-resistant Staphylococcus aureus (MRSA). This risk can be minimized with the use of antibiotic laden allograft (ALA) via iontophoresis. Ceftaroline fosamil (CF) is an advanced-generation cephalosporin, an alternative treatment for MRSA infections. Its antibacterial activity and safety profile are better than vancomycin. CF iontophoresed bone has not been used before. This study was conducted to establish the feasibility of creating a CF ALA and establish the prime conditions for its expenditure. Method: We created an iontophoresis cell; 3% CF was inserted within medullary segment of goat bone and sealed from external saline solution. The cell operated at the following voltages 30, 60 and 90 V and at the following durations 5, 10, 15, 20, 25 and 30 min. Information regarding optimal conditions for its application was then obtained. After which, correlation between voltages and time with CF concentration in the bone was analysed. A bioavailability test was also conducted to observe the optimal rate of CF elution from the graft. Result: The optimal condition for the impregnation process is 3% CF at 90 V for 10 min. Bone graft impregnated with CF at optimal conditions can elute above minimum inhibitory concentration of the CF against MRSA for 21 days. Conclusion: CF iontophoresis was found feasible for allograft impregnation. The technique is simple, inexpensive and reproducible clinically. Iontophoresis offers a novel solution to reduce the rate of perioperative infection in reconstructive surgery involving use of bone graft.